PELAKSANAAN PERJANJIAN SEWA -MENYEWA KEBUN DI DESA POMPENGAN KECAMATAN LAMASI TIMUR TINJAUAN EKONOMI ISLAM - Arafat, H Muammar; Puspa, Puspa (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
It is undeniable that leasing transactions are common in the community. Renting is basically permissible in Islam, because basically human beings are always constrained by limitations and shortcomings. Therefore, humans between one and the other are always bound and need each other, and renting is one of the applications of limitations that are needed by humans in social life. However, if viewed from the nature of speculative renting a garden, it means that there is no certainty whether the plantation will succeed or not at all produce in large or small quantities, then this element of uncertainty cannot be justified in Islamic law.